Application of Area to Point Kriging to Buruli Ulcer Incidence in Ashanti and Brong Ahafo Regions of Ghana - Ossei, Linda (2013)
A thesis submitted to the Institute of Distance Learning, Kwame Nkrumah University of Science and Technology in partial fulfilment of the requirement for the award of Master of Science degree in Industrial Mathematics, August-2013